Penilaian Keberhasilan Reklamasi Pada Pit Serujan Utara PT. IMK Kabupaten Murung Raya - Fahrul Indrajaya; Marlen Fince T. L.; Neny Fidayanti; Yossa Yonathan Hutajulu (PROMINE, 2020)
PT. IMK is located in Murung Raya Regency, Central Kalimantan Province, which is engaged in gold and silver mining with an area of 47.940 hectares contract. The purpose of this study is to assess the reclamation activities that have been done in the Serujan Pit. The implementation of reclamation in PT. IMK begins with the stage based on the decree of the Minister of Energy and Mineral Resources Number : 1827 K/30/MEM/2018 on the guidelines of good mining engineering regulations. The parameters used in assessing the success of reclamation are land utilization, revegetation, and finishing. The results of the success criteria derive the score value and the weights used as the basis of the assessment. Based on the results of the reclamation assessment obtained by the total value of 93.33%, with a good category (reclamation results are acceptable).